(untitled) (Journal of Information Technologies in Education (ITE), 2011)
Considered the problem of organizing the independent work of students in preparing for occupations in the process of what happens systematization of knowledge, and to activate the creative work of students, develops the ability to use ICT in science. The technique of lectures in the form of analysis of the material presented in lecture notes, and developing dynamically changeable lecture material to promote the interest, activity and independence of students with learning it